RELIGIOUS MULTICULTURALISM: A CHALLENGE ON WEST AFRICAN HUMAN DEVELOPMENT EFFORTS - Mujtahidah, Ida (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The development of human resource potential which requires a maximum set of supporters. Not onlythe economic and political stability but also support social elements. The continent of Africa in particularWest African region is an area that is composed of different cultures or different religions. Not onlyChristian and muslim relations but today is precisely coupled with strife Wahhabism that trigger strifewith sunni and Shia and more. The challenges faced by tribes or Nations in the West African countriesis also related to diversity. This paper will discuss the African community in developing their potentialfor the sake of development of the country. The method used is a research library with chaos theory as aframework for analysis. The results showed that West African countries with a high potential of resourcesbut have a tenuous bond between culture and tribal practices are high it is difficult to develop existingresources to the maximum.Keyword: west africa, multiculturalism, human resources development, religious affairs.